The value of serum Mac-2 binding protein glycosylation isomer in the diagnosis of liver fibrosis: a systematic review and meta-analysis - Liu, Xinyu; Zhang, Wei; Ma, Baofeng; Lv, Chunlei; Sun, Mimi; Shang, Qinghua (Frontiers in Physiology, 2024)
The early detection and intervention of liver fibrosis (LF) in patients with chronic liver disease is critical to their management. The accuracy of serum Mac-2 Binding Protein Glycosylation Isomer (M2BPGi) in the diagnosis of LF remains controversial. This study aimed to comprehensively assess the value of serum M2BPGi in diagnosing LF.The PubMed, Embase, MEDLINE, Web of Science, and Cochrane Library databases were searched. The effect values were combined using a random-effects model. Meta-regression and subgroup analysis were used to explore the sources of heterogeneity. In addition, publication bias assessment and sensitivity analysis were conducted.Results: This study includes 12 studies with 2416 patients. The pooled sensitivity, specificity and AUROC of M2BPGi in the diagnosis of significant fibrosis (≥ F2) were 0.65 (95% CI: 0.57-0.71), 0.79 (95% CI: 0.72-0.84) and 0.78(95% CI: 0.74-0.81), respectively, while those for predicting extensive fibrosis (≥ F3) were 0.76 (95% CI: 0.71-0.80), 0.75 (95% CI: 0.68-0.81) and 0.81(95% CI: 0.77-0.84). Sensitivity analysis indicated stable results in this study. The disease type, cut-off values, study country, average age and male proportion were the sources of heterogeneity in diagnosing significant fibrosis of M2BPGi (P < 0.05). And the sample size, disease type, study country, publication year, cut-off values, average age, and male proportion were important sources of heterogeneity in diagnosing extensive fibrosis (P < 0.05).Conclusions: Serum M2BPGi has good diagnostic performance for significant fibrosis and extensive fibrosis in patients with CHB, CHC or NAFLD, and is an effective, non-invasive, and convenient marker.